Bayyinah Nurrul Haq INOVASI PRODUK PADA PERKULIAHAN STUDIO DI PROGRAM STUDI DESAIN PRODUK UNIVERSITAS TRILOGI JAKARTA - Bayyinah Nurrul Haq (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
This paper will discuss the lectures of product design studios from the perspective of the resulting productinnovation. Referring to the product innovation model proposed by Lucia Rampino (2016), product innovationconsists of functional innovation, aesthetic innovation, meaning innovation, and product typology innovation.Product Design Trilogy University applies 5 times studio courses, which are carried out from semester 3 tosemester 7. Each level has a different theme, complexity, and application flow design process. Based onobservations, interviews with lecturers and students, innovation achievements of results and processes lecturesfound the application of different innovation priorities. This is due to the emphasis on the theme of studioassignments, student conditions, lecture conditions.